Dynamic labor demand in China: public and private objectives. (September 2015) - Cooper, Russell; Gong, Guan; Yan, Ping
<x xml:space="preserve">Abstract</x> This article studies dynamic labor demand by private and public manufacturing plants in China. The analysis uncovers the objectives of public and private enterprises and estimates labor adjustment costs by ownership. Public plants maximize the discounted present value of profits without a soft budget constraint. There is strong evidence of quadratic and linear firing costs at the plant level. The higher quadratic adjustment costs of the public plants may reflect their internalization of social costs of employment adjustment. Domestic private plants and collective plants have about the same discount factor, much lower than state‐controlled plants.